2011
DOI: 10.1063/1.3566002
|View full text |Cite
|
Sign up to set email alerts
|

Quantum decoherence in finite size exciton–phonon systems

Abstract: Based on the operatorial formulation of the perturbation theory, the properties of a confined exciton coupled with phonons in thermal equilibrium is revisited. Within this method, the dynamics is governed by an effective Hamiltonian which accounts for exciton-phonon entanglement. The exciton is dressed by a virtual phonon cloud whereas the phonons are clothed by virtual excitonic transitions. Special attention is thus paid for describing the time evolution of the excitonic coherences at finite temperature. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 59 publications
(80 reference statements)
1
39
1
Order By: Relevance
“…The entanglement results from a dual dressing effect because a state |k defines an exciton dressed by a virtual phonon cloud whereas a number state |n p describes phonons clothed by virtual excitonic transitions. The behavior of the energy corrections has been studied in great details [56][57][58]. Owing to the dressing, we have shown that the excitonic eigenenergies are redshifted and the energy correction of a stationary wave |k scales as…”
Section: B Perturbation Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…The entanglement results from a dual dressing effect because a state |k defines an exciton dressed by a virtual phonon cloud whereas a number state |n p describes phonons clothed by virtual excitonic transitions. The behavior of the energy corrections has been studied in great details [56][57][58]. Owing to the dressing, we have shown that the excitonic eigenenergies are redshifted and the energy correction of a stationary wave |k scales as…”
Section: B Perturbation Theorymentioning
confidence: 99%
“…As shown previously [57], the decoherence factor behaves as a gaussian function whose time evolution can be extracted from the short-time limit of Eq. (20).…”
Section: A Approximate Expression Of the Exciton Densitymentioning
confidence: 99%
See 3 more Smart Citations